Philippines pagdaloy, flow of life. (The National Commission for Culture and the Arts International Information and Networking Centre for Intangible Cultural Heritage in the Asia-Pacific Region, 2016)
Collection of audiovisual materials presenting the culture of ethnic groups in the Philippines.